Design of Fractional Order PID controller for liquid level control of spherical tank - Sundaravadivu, K.; Arun, B.; Saravanan, K. (2011 IEEE International Conference on Control System, Computing and Engineering, 2011)
In this paper, Fractional Order Proportional Integral Derivative Controller (FOPID) is designed for liquid level control of a spherical tank which is modeled as a First Order Plus Dead Time (FOPDT) system about an operating point. The response of designed FOPID controller is compared with the traditional integer order PID (IOPID) controller in simulation and with IOPI controller on experimental setup. The PI λ D μ controller is designed using minimization of Integral Square Error (ISE) method. This method offers a practical and systematic way of the controllers design for the considered class of FOPDT plant. From the simulation and experimental results presented, the designed fractional order controller works efficiently with improved performance comparing with the integer order controller.